Determination of Total Phenolic Content and Antioxidant Activity of Roselle (Hibiscus sabdariffa L.) Calyx and Epicalyx Ethanolic (Alcoholic) Extract - Sirag, Nizar; MM, Elhadi; Algaili, Algaili M; Ohaj, Mohamed (Gezira Journal of Health Sciences; Vol 10 No 1 (2014), 2014)
Background : Medicinal plants contain physiologically active ingredients that over the years have been exploited in traditional medicine for the treatment of various ailments.  Objectives: This study was undertaken to investigate the total phenolic content and antioxidant capacity of Roselle ( Hibiscus sabdariffa ) calyx and epicalyx ethanolic extract.  Methods : The total phenolic content was estimated by Folin Ciocalteau method using gallic acid as standard while the antioxidant capacity was determined based on the plant extract to scavenge DPPH radical. Results : The total phenolic content was found to be 41.07 mg gallic acid equivalent /g .The extract exhibited a significant measurable dose dependent inhibition of the DPPH activity. At a concentration of 250µg/ml, sabdariffa calyx epicalyx ethanolic extract scavenged 86% of DPPH radical whereas 125 and 50 µg/ml caused 53% and 23% DPPH inhibition respectively and a very mild inhibition was produced at a concentration of 5 µg/ml.  Conclusion : It can be concluded that sabdariffa calyx epicalyx ethanolic could be a potential source of antioxidant principles.